2016
DOI: 10.1155/2016/2895972
|View full text |Cite
|
Sign up to set email alerts
|

The Markers of Glutamate Metabolism in Peripheral Blood Mononuclear Cells and Neurological Complications in Lung Cancer Patients

Abstract: Objective. To evaluate the involvement of glutamate metabolism in peripheral blood mononuclear cells (PBMC) in the development of neurological complications in lung cancer and during chemotherapy. Methods. The prospective study included 221 lung cancer patients treated with chemotherapeutics. Neurological status and cognitive functions were evaluated at baseline and after 6-month follow-up. Glutamate level, the activities of glutaminase- (GLS-) glutamate synthetizing enzyme, glutamate dehydrogenase (GDH), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A growing body of evidence shows that GLS1 was highly expressed in a various of human tumor cells such as triple‐negative breast cancer, lung cancer, oral squamous cell carcinoma, human hepatoblastoma, acute myeloid leukemia. and gastroenteropancreatic cancer . Over expression of GLS1 presented high proliferation rate in tumors such as gliomas and non‐small‐cell lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that GLS1 was highly expressed in a various of human tumor cells such as triple‐negative breast cancer, lung cancer, oral squamous cell carcinoma, human hepatoblastoma, acute myeloid leukemia. and gastroenteropancreatic cancer . Over expression of GLS1 presented high proliferation rate in tumors such as gliomas and non‐small‐cell lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we found that rats treated with 5-FU lack inhibitory control [12]. Additionally, treatment with carboplatin, another commonly used chemotherapeutic agent associated with chemobrain [26], not only impaired working memory [12], but also decreased neurotransmitter release [19]. The current study tested effects of 5-FU on attention, a fundamental component of EF.…”
mentioning
confidence: 80%
“…47 Physical interaction of glutamate and T cells has been demonstrated using radio-labelled glutamate. 48 In addition to elevated glutamate levels in white brain matter of patients with multiple sclerosis, 49 glutamate levels were found to be elevated in plasma of patients with several immune diseases, including HIV infection, 50,51 cancer, 52,53 and rheumatoid arthritis. 54,55 Here, glutamate, NMDA and QA were all used to examine NMDA-R function in peripheral human CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%